DISIPLIN KERJA DITINJAU DARI KOMITMEN ORGANISASI PADA SATUAN KERJA BIRO LOGISTIK POLDA JAWA TENGAH - Ichsan Dicky Wicaksana; I Rheny Arum Permitasari (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas AKI Semarang, 2023)
Discipline is the most important thing that must be owned by an employee, one of the factors that influence work discipline is organizational commitment. Therefore this study aims to determine the relationship between organizational commitment and work discipline in members of the Police Logistics Bureau of the Central Java Regional Police. The sample used was members of the Logistics Bureau of the Central Java Regional Police, totaling 200 people. The sampling technique used is incidental random sampling technique. The data analysis used is Spearman's correlation. The results of this study indicate that there is a very significant relationship between organizational commitment and work discipline in members of the Police Logistics Bureau of the Central Java Regional Police. This is shown from the value of the coefficient Ïƒ = 0.619 with a significance = 0.000 (p <0.01) which means that there is a very significant relationship between organizational commitment and work discipline which is shown from a significance value of <1%, and this means that the hypothesis submitted is acceptable. The magnitude of the influence of organizational commitment on work discipline in members of the Logistics Bureau of the Central Java Regional Police is shown from the value of the coefficient of determination R2 = 38%.